A comparative study between open versus closed method of creation of pneumoperitoneum in laparoscopic surgeries - Kumar Singh, Deepak; Desai, Hridyanath; Patel, Rushit; Kamath, Narayan; Amin, Nadeem; Patel, Kiran (Journal of Neonatal Surgery, 2025)
Background: Gaining access to the peritoneal cavity is a critical step in laparoscopic surgeries and is associated with the risk of complications. The two most commonly used techniques for pneumoperitoneum creation are the open (Hasson cannula) and closed (Veress needle) methods. This study aims to compare these techniques in terms of procedural efficiency, intraoperative and postoperative complications, and long-term outcomes. Methods: This randomized controlled trial included 50 patients undergoing elective laparoscopic surgeries at a tertiary care hospital. Patients were randomized into two groups: 25 underwent the open technique, and 25 underwent the closed technique. Key parameters, including time for pneumoperitoneum creation, number of attempts, intraoperative complications, postoperative outcomes, and follow-up findings over three months, were recorded and analyzed using appropriate statistical methods. Results: The open technique demonstrated a significantly shorter duration for pneumoperitoneum creation (101.54 seconds vs. 122.58 seconds; p<0.01) and surgical access (6.68 minutes vs. 7.96 minutes; p<0.01). The mean total procedure time was also lower in the open group (118.24 minutes vs. 142.48 minutes; p<0.01). Gas leaks were more frequent in the open group (32% vs. 8%; p=0.024), while port-site hemorrhage occurred in 8% of open group cases but was absent in the closed group (p=0.49). No significant differences were observed in postoperative complications such as port-site infections (8% vs. 0%; p=0.49) or bleeding (16% vs. 4%; p=0.34). Long-term complications, including wound infections and port-site hernias, were absent in both groups during the three-month follow-up. Conclusions: Both the open and closed techniques are safe and effective for pneumoperitoneum creation. The open technique offers significant time-saving advantages but is associated with a higher incidence of minor complications, such as gas leaks and port-site hemorrhage. The choice of technique should be guided by patient-specific factors, surgeon expertise, and procedural requirements. Further large-scale studies are needed to provide definitive recommendations for clinical practice.